Transitions to sustainable management of phosphorus in Brazilian agriculture - Withers, Paul J. A.; Rodrigues, Marcos; Soltangheisi, Amin; De Carvalho, Teotonio S.; Guilherme, Luiz R. G.; Benites, Vinicius De M.; Gatiboni, Luciano C.; De Sousa, Djalma M. G.; Nunes, Rafael De S.; Rosolem, Ciro A. [UNESP]; Andreote, Fernando D.; Oliveira, Adilson De; et al. (Springer Nature, 2018)
Brazil's large land base is important for global food security but its high dependency on inorganic phosphorus (P) fertilizer for crop production (2.2 Tg rising up to 4.6 Tg in 2050) is not a sustainable use of a critical and price-volatile resource. A new strategic analysis of current and future P demand/supply concluded that the nation's secondary P resources which are produced annually (e.g. livestock manures, sugarcane processing residues) could potentially provide up to 20% of crop P demand by 2050 with further investment in P recovery technologies. However, the much larger legacy stores of secondary P in the soil (30 Tg in 2016 worth over $40 billion and rising to 105 Tg by 2050) could provide a more important buffer against future P scarcity or sudden P price fluctuations, and enable a transition to more sustainable P input strategies that could reduce current annual P surpluses by 65%. In the longer-term, farming systems in Brazil should be redesigned to operate profitably but more sustainably under lower soil P fertility thresholds.